2015
DOI: 10.5194/amt-8-2183-2015
|View full text |Cite
|
Sign up to set email alerts
|

Estimating reflectivity values from wind turbines for analyzing the potential impact on weather radar services

Abstract: Abstract. The World Meteorological Organization (WMO) has repeatedly expressed concern over the increasing number of impact cases of wind turbine farms on weather radars. Current signal processing techniques to mitigate wind turbine clutter (WTC) are scarce, so the most practical approach to this issue is the assessment of the potential interference from a wind farm before it is installed. To do so, and in order to obtain a WTC reflectivity model, it is crucial to estimate the radar cross section (RCS) of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Values for RCS calculated by detailed modeling of a typical wind turbine (Angulo et al 2015) are in the scope of 49-68 dB. The residual signal after standard Doppler filtering depends on configurable filter attenuation and on the distance between radar and turbine.…”
Section: Discussion Of Some Aspects Of the Proposed Model 41 Neglecmentioning
confidence: 99%
See 1 more Smart Citation
“…Values for RCS calculated by detailed modeling of a typical wind turbine (Angulo et al 2015) are in the scope of 49-68 dB. The residual signal after standard Doppler filtering depends on configurable filter attenuation and on the distance between radar and turbine.…”
Section: Discussion Of Some Aspects Of the Proposed Model 41 Neglecmentioning
confidence: 99%
“…), the turbine itself (shape and materials), weather radar components (antenna, electronic parts, signal processing), and their relative movement etc. (Bobillot et al 2012) At the other end there are very simplified models based on theoretical simulations of RCS (Radar Cross Section) of a typical, idealised (and simplified) turbine model, converted into radar reflectivity with the assumption that the whole wind turbine is included within the radar beam (Angulo et al 2015). The first approach requires a lot of effort and powerful computers to reach its results and has to be performed when the coexistence of wind farm and weather radar is unavoidable, and we also have to be aware of the detailed impact on different radar products.…”
Section: Introductionmentioning
confidence: 99%
“…Large array-arranged wind turbines would induce serious reradiation interference to nearby radar stations, due to the site conflict between wind farm and radar stations [1][2][3]. According to the basic radar equation, a way for suppressing this interference by reducing the radar cross-section (RCS) on wind turbine side was proposed [4,5]. In addition, the rotational motion of the wind turbine blades will cause the RCS to change with time.…”
Section: Introductionmentioning
confidence: 99%
“…By directing the radar towards the wind turbines, they found that the turbines give rise to complex but characteristic patterns in the time-frequency domain. Mitigation schemes, based on the observed spectral characteristics of wind turbines, have (Gallardo et al, 2008;Bachmann et al, 2010a, b). However, to observe the characteristic pattern of a wind turbine in the frequency domain, the radar should dwell on the target for a period of time.…”
Section: Introductionmentioning
confidence: 99%